Ideational meanings of science and interpersonal position of readers in science textbooks for basic level in Indonesia - Hermawan, Budi; Rahyono, F.X (Universitas Pendidikan Indonesia, 2019)
This paper investigates the ideational meanings of science through the analyses of types and functions of the images used in science textbooks, the formality of the pictures, the genre of the texts used as the main passage, and the process types used. This paper also probes into the interpersonal meaning of science through the analysis of pronouns used to address the readers, the analysis of represented participants, including the existence or nonexistence of gaze, and the position of the images in relation to their interactive participants. The data for the study consisted of three randomly selected topics from science textbooks for grade 7,8 and 9 based on two different curricula used, namely KTSP 2006 and Kurikulum 2013. Reading images as proposed by Kress and van Leeuwen (1996; 2006) was used to analyze the visual images along with systemic functional linguistics (SFL) as proposed by Halliday (1994); Halliday and Matthiessen (2004) to analyze the verbal texts. The findings show that ideationally, the most dominant type of pictures used in the topics investigated is realistic pictures, pictures which represent human optical perception. In terms of the function of the pictures, analytical pictures, pictures which show the part-whole relationship, are dominantly used in the topics. Ideationally, the topics in the textbooks maintain the sameness of forms and colors of the scientific objects students study at schools as their real objects. Interpersonally, readers are positioned as the receivers of the message from persons who are more knowledgable, hence, more powerful than they are but, at the same time, approachable by the readers.